Utilização de um floco-decantador de manta de lodo para o tratamento de efluentes de piscicultura em tanque - De Souza, Thassya Geórgia Lucas [UNESP]; Matsumoto, Tsunao [UNESP]; Ortiz, Iván Andrés Sánchez (My University, 2015)
Aquaculture is an economic activity in current expansion that requires large volumes of water inits productive process. Fish culture farms in earthen dug ponds produce effluents that in most cases do not receive any treatment before its final discharge, deteriorating the environment. The development of alternatives for treatment of these effluents is required in order to guarantee the conditions established by environmental legislation for their discharge or reuse. This article reports the evaluation of a sludge blanket settler flocculator (SBSF) system associated to a downflow sand filter in the treatment of effluents from a recreational fishing dug pond, located at the Ipê neighborhood (Ilha Solteira-SP, Brazil). Several trials in the experimental scheme using surface loading rates (SLR) of 60, 120 and 180m3·m-2/day were evaluated. The results showed the suitability of the SBSF for impurities removal in fish culture effluents, with best performance for the 120m3·m-2/day SLR. Turbidity, COD, BOD5, total N, total P, total solids, suspended solids, dissolved solids and algae were monitored, and their removal performance by the system were calculated; the average efficiencies were 98.8, 93.2%, 98.6, 41.5, 31.3, 71.2, 86.9, 66.5 and 98.9%, respectively. The proposed system is an alternative for fish culture effluents treatment, which provides to the treated liquid the quality characteristics within the range established by the Brazilian legislation for dumping or eventual reuse.
Utilization of a sludge blanket settler flocculator system on fish culture ponds effluents treatment